2020
DOI: 10.1007/s42058-020-00026-2
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in magnetic resonance imaging of optic neuritis

Abstract: Optic neuritis is a common cause of vision loss, but it is difficult to visualize the lesion well via conventional magnetic resonance imaging due to its small size and oblique orientations of the optic nerves. Some advanced techniques have been introduced into clinical practice in recent decades. Herein we review recent advances in magnetic resonance imaging techniques that are useful in cases of optic neuritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…It has been suggested that both water and fat signals should be suppressed. 5 , 64 For MRI magnetic field strength, 1.5T or 3T is recommended. 5 In the acute phase, the optic nerve is enlarged with a high-intensity signal on T2-weighted imaging and has a contrast effect on post-contrast-enhanced T1-weighted imaging.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that both water and fat signals should be suppressed. 5 , 64 For MRI magnetic field strength, 1.5T or 3T is recommended. 5 In the acute phase, the optic nerve is enlarged with a high-intensity signal on T2-weighted imaging and has a contrast effect on post-contrast-enhanced T1-weighted imaging.…”
Section: Discussionmentioning
confidence: 99%